백내장 수술 시 첫 번째 안의 실제굴절오차의 반영률에 따른 두 번째 안의 실제굴절오차 - 어두리(Doo Ri Eo); 임동희(Dong Hui Lim); 현주(Joo Hyun); 최재환(Jae Hwan Choi); 이민규(Min Gyu Lee); 정의상(Eui Sang Chung); 정태영(Tae Young Chung) (Daihan angwa haghoi jabji, 2016)
목적: 양안 초음파 수정체유화술 및 후방 인공수정체 삽입술을 시행 받은 환자에서 실제굴절오차를 분석하여 첫 번째 수술 후의 실제굴절오차를 두 번째 수술 시에 어느 정도 반영하여야 실제굴절오차를 최소화할 수 있는지를 분석하고자 한다. 대상과 방법: 양안 백내장 수술을 시행 받은 환자 248명을 대상으로 후향적 연구를 시행하였으며, 수술 전에 산출된 예상굴절력의 구면렌즈 대응치와 술 후의 실제굴절력의 구면렌즈 대응치를 비교하였고, 첫 번째 수술 시의 실제굴절오차의 반영률을 계산하여 반영률에 따른 두 번째 수술 시의 실제굴절오차의 범위를 분석하였다. 결과: 첫 번째 수술 시의 IOL Master®를 이용하여 Sanders-Retzlaff-Kraff (SRK)-T, SRK II 공식으로 계산된 예상굴절력과 실제굴절력의 차이가 0.5D보다 큰 경우에 그 차이의 50-60%, 40-50%를 반영하는 것이 두 번째 수술 시의 실제굴절오차를 0.5D 이내로 줄일 수 있는 확률이 제일 높았다(75%, 100%). 결론: 양안 백내장 수술 시, 첫 번째 수술 시의 실제굴절오차를 40-60% 반영하는 것이 두 번째 수술 시의 실제굴절오차를 더 줄일 수 있다. Purpose: To evaluate the reflection rate of the first eye in order to minimize the real refractive error in the second eye in bilateral consecutive cataract surgeries. Methods: A retrospective analysis was performed with 248 patients who underwent bilateral sequential uncomplicated phacoemulsification and posterior chamber intraocular lens implantation. Predicted spherical equivalent was compared with postoperative spherical equivalent, and the range of real refractive error was analyzed by calculating the reflection rate of the first eye. Results: When the difference between predicted spherical equivalent and postoperative spherical equivalent was greater than 0.5 D as calculated with the formula of Sanders-Retzlaff-Kraff Theoretical (SRK)-T and SRK II, application of 50-60%, 40-50% of the difference of the first eye was high probability to reduce the second-eye real refractive error (75%, 100%). Conclusions: Application of 40-60% of the real refractive error in the first-eye can minimize the real refractive error in the second- eye in bilateral sequential cataract surgeries. KCI Citation Count: 0